2015
DOI: 10.1097/md.0000000000000440
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Training for Colonoscopy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…A subsequent study found comparable experienced-novice differences when a magnetic endoscopic imaging device was used in conjunction with custom software to automate measurement of the colonoscope’s progression through the synthetic colon 14. The final study replicated the experienced-novice differences in procedure time, and also demonstrated experience-level effects for a novel suite of observational metrics used in conjunction with the model 15. Such comparisons between user-groups known to have differing levels of experience are a common means of generating evidence for the construct validity of metrics associated with the use of a simulation device; that is, the replication of real-world performance differences implies that the simulation taps into the skill that the metrics purport to measure 23.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…A subsequent study found comparable experienced-novice differences when a magnetic endoscopic imaging device was used in conjunction with custom software to automate measurement of the colonoscope’s progression through the synthetic colon 14. The final study replicated the experienced-novice differences in procedure time, and also demonstrated experience-level effects for a novel suite of observational metrics used in conjunction with the model 15. Such comparisons between user-groups known to have differing levels of experience are a common means of generating evidence for the construct validity of metrics associated with the use of a simulation device; that is, the replication of real-world performance differences implies that the simulation taps into the skill that the metrics purport to measure 23.…”
Section: Introductionmentioning
confidence: 75%
“…Further, evidence from several recent studies supports the construct validity of several performance measures derived from use of the Kyoto Kagaku model for the assessment of insertion skill 13 14 15. The first of these studies showed that, compared with experienced colonoscopists, novices had lower completion rates, took longer to reach the cecum, and (for 2 of the 4 colon cases tested) exerted more force on the colon model 13, mirroring experience-related differences found in real colonoscopy 16 17 18 19 20 21 22.…”
Section: Introductionmentioning
confidence: 84%
“…For example, Tjiam and colleagues established certification standards for residents in laparoscopic urological skills by comparing global ratings of a cohort of staff surgeons and trainees stratified by case volume into expert, intermediate and novice groups. Seventeen articles used fully qualified surgeons and physicians. Pedersen and co‐workers used expert orthopaedic surgeons as the competent group on a hip fracture simulator, and set standards that trainees must reach before progressing to the clinical environment.…”
Section: Resultsmentioning
confidence: 99%
“…Fellows are a unique group of participants, as they can be included under the trainee umbrella, and yet are often experienced operators at procedures tested in standard‐setting exercises. In this review, six articles specified the use of fellows as study participants, and two included medical student participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation